Pipeline problem: factors influencing the under representation of women in the top leadership positions of sport organisations - Aman, Mirian Pabatao; Yusof, Aminuddin; Ismail, Maimunah; Mohamed Razali, Abu Bakar (Universiti Malaysia Pahang, 2018)
National Sport Associations, National and International Sport Federations and even the International Olympic Committee continue to struggle with meeting the 20% representation quota of women in executive boards. Although women’s representation as athletes, coaches and officials has increased in national and international sport competitions, this does not hold in leadership, particularly in top positions. In sport leadership, empirical research showed statistical figures that women have gained access in leadership pipeline however, they still lack representation on executive boards. This study is a part of a larger phenomenological investigation intended to identify the factors that influence the persistent underrepresentation of women in top leadership positions. From a purposive maximum variation sampling of seven participants, top women leaders in Malaysia national sport organisations were interviewed about their career paths and experiences concerning how and why women top leaders continue to lag behind their male counterparts. Results suggest that self-limiting behaviors, work-life conflict and interpersonal relationships among other women contribute to the underrepresentation of women in top positions. Factors attributed to social perception of gender and leadership roles incongruence also limited women leaders’ access in organisations, which subsequently contribute to the pipeline problem. Moreover, participants offered suggestions in overcoming the challenges and personal strategies in advancing opportunities and career development.